Field reports of Iowa birds, fall 1988 documentations, December 9, 1988 - Dinsmore, James J.et al; Dinsmore, Stephen J.et al; Kent, Thomas H. (Thomas Hugh), 1934-et al; Armstrong, Eloiseet al; Armstrong, Eugeneet al; Bray, Tanyaet al; Cornett, Dorothy M.et al; Engebretsen, Beryet al; Fuller, James L.et al; Grenon, Alan G.et al; Kanago, Dixieet al; Moore, Francis L.et al; et al. (1988)
List of birds and locations across the state. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed